An examination of students’ perceptions of goal orientation in the classroom and teachers’ beliefs about intelligence and teacher efficacy - Siebert, Mary Catherine (Kansas State University, 2006)
The purpose of this study was to examine secondary-level social science teachers’ reported implicit beliefs about intelligence as measured by Dweck’s Theories of Intelligence Survey, and teachers’ levels of efficacy as measured by Gibson and Dembo’s Teacher Efficacy Survey, in relation to their students’ perception of goal orientation in the classroom as measured by Midgley’s PALS Survey in the classroom. In addition, this study examined the relationship of students’ gender and self-perceptions of ability to self reported classroom goal orientation. Participants in this study were high school social science teachers teaching in 17 schools in northeast Kansas (N = 63), and their students enrolled in social science classes (N = 1,214). The survey instruments were administered during the Spring 2006 semester during regularly scheduled courses. Data were analyzed using Pearson product-moment correlations, multiple regression, and other statistical techniques. A statistical level of p < .05 was used for all tests conducted. Five statistical tests were conducted. Three of the statistical tests utilized the Pearson product moment correlation: (1) correlation between teachers’ implicit theories of intelligence and self-efficacy, (2) correlation between teachers’ implicit theories of intelligence and students’ perception of goal orientation in the classroom, (3) correlation between teachers’ self-efficacy and students’ perception of the classroom goal orientation. Two statistical tests utilized multiple regression analysis: (1) regression analysis examining teachers’ implicit theories of intelligence and teachers’ self-efficacy as a predictor of students’ perception of the classroom goal orientation, and (5) regression analysis examining students’ gender and rating of ability as predictors of students’ perceptions of goal orientation in the classroom. A positive correlation was found between teachers’ theories of intelligence and self-efficacy. A statistical significance was also found for the relationship between teachers’ self-efficacy and their students’ perceptions of the classroom goal orientation based on teachers’ theories of intelligence or self-efficacy. Statistical significance was not found for students’ ability rating, as a predictor of their perception of the classroom goal orientation. Statistical significance was found for gender as a predictor of students’ perception of the classroom goal orientation, however, practical significance is questionable. Several suggestions for additional research and improvement in practice with regard to teachers’ belief systems and student goal structures were offered. This research provides additional data for teachers and school leaders in helping them understand the role of teachers’ belief systems in fostering student achievement.
Keywords: goal orienttion; theory of intelligence; Education, Curriculum and Instruction (0727)